Determinants of a 3-min all-out upper body poling exercise in elite cross-country skiers - Hegge, A. M.; Ettema, G.; Sandbakk, O. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
A high aerobic capacity, efficient technique and specific power are regarded as important determinants in middle distance sports, such as middle distance running (i.e., leg exercise) and cross-country sprint skiing (i.e., whole body exercise). Crosscountry skiing involves combined upper and lower body exercise, where the upper body has an important role. Upper body power is strongly related to cross-country skiing performance, but to date, very little is known about the performance-predicting factors in isolated upper body poling movements. This study tested the hypothesis that the aerobic capacity (VO2peak), gross efficiency and the work produced per cycle would be associated with upper body poling performance.